Rice Beetle, Dyscinetus morator (Fab.) (Insecta: Coleoptera: Scarabaeidae) - Robert E. Woodruff (EDIS)
he rice beetle, Dyscinetus morator (Fabricius) (Figure 1), is a common beetle in the eastern half of the United States, and it is one of the most ubiquitous species taken in blacklight traps during much of the year. It appears to be only a minor pest, but it is often brought to the homeowner's attention because of the large quantities found around lights. This document is EENY-102, one of a series of the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date July 1999. Reviewed May 2003.